Pemetaan Daya Dukung Lingkungan Lahan Basah Desa Tanjung Buka Dalam Penyediaan Air dan Pangan - Adi Sutrisno (Borneo Engineering : Jurnal Teknik Sipil, 2023)
Changes in land cover caused by development activities carried out by humans have occurred a lot in Indonesia. It can cause a decrease in the carrying capacity of the environment. Therefore, this study aimed to assess the status of the environmental carrying capacity of the Tanjung Buka Village wetland, geographically located at 117°21'0" - 117°40'0" EL and 2°50'0" - 3°0'0" NL, where the land cover has changed many times due to development activities. The status assessment uses an ecosystem service approach with a simple, weighted approach to mathematical modeling, by using landscape, vegetation type, and land cover parameters. The results showed that: (1) The Tanjung Buka Village wetland ecosystem is dominated by the "very low" category (26,968.70 or 62.31%) of its ecosystem services as a provider of fresh water. It means its carrying capacity is "very low" in the fresh water supply, used continuously. At the same time, Food providers tend to be in the "high" category (20,917.47 ha or 48.33%), which means that in general, the carrying capacity of the Tanjung Buka Village wetland environment is "high" as a food provider that is used continuously. It indicated that the Tanjung Buka Village wetland had changed the land cover, becoming secondary mangroves, secondary swamp forests, ponds, open land, built-up land, mixed gardens and shrubs, so that its carrying capacity becomes “very low” as a provider of fresh water, but in providing food tends to be “high”